Pyeloplasty for Pelvi-Ureteric Junction Obstruction in Malrotated Kidneys in Children - Jayakumar, Sivasankar; Antao, Brice A.; Ninan, George Kaithayil (European Journal of Pediatric Surgery, 2012)
Purpose Pelvi-ureteric junction (PUJ) obstruction associated with malrotated kidney is very rare. In such cases, dismembered pyeloplasty poses technical difficulties. We present our experience with management of PUJ obstruction in malrotated kidneys in children and their outcomes.Methods Retrospective review of case notes of all children who had pyeloplasty for PUJ obstruction associated with malrotated kidneys, over a period of 7 years between January 2003 and December 2009 at our institution.Results We identified four patients, and all four patients had malrotated kidneys with a lateral and slightly inferior facing renal pelvis. Anderson and Hynes dismembered pyeloplasty with inferior pelvi-ureteric anastamosis was performed in two patients (one patient with nephropexy and one patient without nephropexy), but failed to improve the drainage across the PUJ in both the patients. The remaining two patients underwent a dismembered pyeloplasty with anterior pelvi-ureteric anastamosis that resulted in a good drainage. One of the patients who had pyeloplasty with inferior pelvi-ureteric anastamosis had a redo pyeloplasty with anterior pelvi-ureteric anastamosis that restored the drainage adequately.Conclusion In our experience dismembered pyeloplasty with inferior pelvi-ureteric anastamosis along with or without nephropexy has not been successful in cases of PUJ obstruction in laterally malrotated kidneys. Although the number of cases in our study is small, we have had a 100% success with dismembered pyeloplasty with anterior pelvi-ureteric anastamosis. The authors are of the opinion that this modified approach is recommended as a viable option both as a primary and salvage procedure for PUJ obstruction in laterally malrotated kidneys.
Keywords: malrotation of kidney; pyeloplasty in malrotated kidneys; children; PUJ obstruction; pyeloplasty